Characterization of Full Pore and Stress Compression Response of Reservoirs With Different Coal Ranks - Lu, Jielin; Fu, Xuehai; Kang, Junqiang; Cheng, Ming; Wang, Zhenzhi (Frontiers in Earth Science, 2021)
The accurate characterization of coal pore structure is significant for coalbed methane (CBM) development. The splicing of practical pore ranges of multiple test methods can reflect pore structure characteristics. The pore\fracture compressibility is the main parameter affecting the porosity and permeability of coal reservoirs. The difference in compressibility of different coal rank reservoirs and pore\fracture structures with changing stress have not been systematically found. The pore structure characteristics of different rank coal samples were characterized using the optimal pore ranges of high-pressure mercury intrusion (HPMI), low-temperature liquid nitrogen adsorption (LT-N2A), low-pressure carbon dioxide adsorption (LP-CDA), and nuclear magnetic resonance (NMR) based on six groups of different rank coal samples. The compressibility of coal matrix and pore\fracture were studied using HPMI data and NMR T2 spectrum under effective stress. The results show that the more accurate full pore characterization results can be obtained by selecting the optimal pore range measured by HPMI, LT-N2A, and LP-CDA and comparing it with the NMR pore results. The matrix compressibility of different rank coal samples shows that low-rank coal > high-rank coal > medium-rank coal. When the effective stress is less than 6 MPa, the microfractures are compressed rapidly, and the compressibility decreases slowly when the effective stress is more than 6 MPa. Thus, the compressibility of the adsorption pore is weak. Nevertheless, the adsorption pore has the most significant compression space because of the largest proportion in different pore structures. The variation trend of matrix compressibility and pore\fracture compressibility is consistent with the increase of coal rank. The compressibility decreases with the rise of reservoir heterogeneity and mechanical strength. The development of pore volume promotes compressibility. The research results have guiding significance for the exploration and development of CBM in different coal rank reservoirs.